Financial and legal aspects of the state budget and its role in the budget system of Ukraine - Shevchuk, Oksana; Fedyshin, Olha (Actual problems of law (Aktual'ni problemi pravoznavstva), 2019)
The article deals with the actual problems of legal regulation of the financial system. The category "state budget" as a means of determining the content of the financial system is analyzed. It is established that the state interests are the basis of the formation of a subsystem of public finance with fixed assets: the state budget as the main plan for the formation and use of financial resources to ensure the implementation and functioning of the state. The Budget Code, which can be based on the general logic of construction and regulation of the public finance management system, defines the basic rules for the adoption and implementation of management decisions in each of the articles, as well as requirements for information and analytical support of the state process in Ukraine.The aim of the work is to study the financial and legal aspect of the state budget and determine its role in the budget system of Ukraine. The object of research is the financial and legal aspect of the state budget and its role in the budgetary system of Ukraine. The subject of the study is the peculiarities of the financial and legal aspect of the state budget and its role in the budgetary system of Ukraine.    In order to ensure that the financial legal aspect of ensuring the state budget meets the requirements of the domestic development of Ukraine, it is necessary to make a number of significant changes to the Budget Code of the State and then, on the basis of the proposed changes, to improve the entire budget system.